The Effect of Entrepreneurship Learning and Adversity Intelligence on Students' Entrepreneurial Intentions - Sri Kumala Dewi (Outline Journal of Education, 2022)
This study aims to determine the effect of entrepreneurial learning and adversity intelligence on entrepreneurial intentions Student, this type of research is an ex post facto. the technique of data collection uses observation, documentation and questionnaires. Sampling in this study was carried out by total sampling technique. Data analysis techniques used normality test, multiple linear analysis, t test, F test and determination Based on data analysis using the SPSS 22 program, the equation Y = 21,394 + 0,213X1 + 0,574X2 + e is obtained, then the Entrepreneurship Learning variable (X1) has a partially significant influence on Entrepreneurial Intention with a value of tcoun thitung >ttabel (3,490>1,661) and value sig (0.001 <0.05). While adversity intelligence (X2) has a partially significant influence on Entrepreneurial Intention with a value of tcoun thitung>ttabel (6.462>1.661) and sig value (0.000<0.05). Together, Entrepreneurship Learning and Adversity Intelligence have a significant influence on Entrepreneurial Intention with sig <0.05 or 0,000 <0.05. The contribution percentage of Entrepreneurship Learning and Adversity Intelligence to Entrepreneurial Intention is 59.5%. From the analysis, it can be concluded that entrepreneurship learning and adversity intelligence have an effect on and significantly on the intention of student entrepreneurship.